Physical and Chemical Characteristics of Etawa Crossbred Goat Colostrum in Bogor - Fadliah, M.; Taufik, E.; Arief, I. I. (Jurnal Ilmu Produksi dan Teknologi Hasil Peternakan, 2017)
Goat milk colostrum possess nutritional compounds essential for health, so that its quality needs to be considered by producers and consumers in order to be utilized safely and healthy. However, the information about Etawa crossbred goat colostrum quality especially in Bogor is limited. The aims of this study were to determine the physical and chemical qualities of Etawa crossbred goat colostrum in Bogor. Colostrum samples were taken from two different dairy goat farms namely Bangun Karso Farm, Cijeruk, Bogor (P1) and Yulianto Farm, Cibeteung Udik, Bogor (P2). Fat, protein and lactose contents, solid non fat (SNF), freezing point, pH and aw values were analyzed by different test of Mann-Whitney U test through SPSS statistics program. The results showed that there were significant differences (P <0.05) in fat, protein and lactose contents, SNF, freezing point, pH value and aw of colostrum between two farms. Based on the exiting data on the composition of dairy goat colostrum, fat, protein and lactose contents, SNF, pH value and aw of Etawa crossbred goat colostrum from bogor were in the range of these data.